Geometry optimization for a rectangular corrugated tube in supercritical water reactors (SCWRs) using alumina-water nanoﬂuid as coolant. (15th April 2021) - Behzadnia, Hadi; Jin, Hui; Najafian, Mahyar; Hatami, Mohammad
Abstract: In this paper, a novel rectangular corrugated tube is proposed for the cooling application in supercritical water reactors (SCWRs), numerically. Standard k-ε turbulence model from ANSYS-FLUENT commercial software is used for the simulation. Alumina-water is used as the nanofluid for the cooling in supercritical conditions and tried to find the optimized geometry to reach maximum heat transfer efficiency. Three geometry parameters are considered and by Central composite design (CCD) possible geometries (11 Cases) were designed and optimized by the Response Surface Method (RSM). As the main outcome, parameters a and c had more effects on the Nusselt number and nanoparticles with ϕ = 0.01 reported greatest Nusselt numbers. Also, by increasing the nanoparticles concentration from 0.01 to 0.04, the Nusselt number was decreased by 26.29% due to decreasing the heat capacity of SCW. Highlights: A rectangular corrugated tube is proposed for super-critical water reactor (SCWR). Alumina-water is used as the nanofluid for the cooling in SCWR. Geometry is optimized to reach maximum heat transfer efficiency. Geometries are considered and by Central composite design (CCD). Nusselt number was 26.29% decreased by increasing the nanoparticles concentrations.